O Exame Nacional do Ensino Médio e sua influência nas práticas de letramento em Línguas Inglesa - Ludmila Correa Pinto Rodrigues (2018)
The process of entering a federal university used by Ministério da Educação (MEC) in Brazil, known as Sistema de Seleção Unificada (SISU), promotes, through Exame Nacional do Ensino Médio (ENEM) (BRAZIL, 2009), the selection of students to the federal universities in Brazil and contemplates foreign languages since the 2010 edition.According to the resolution of the Matriz de Referencia do MEC, para o ENEM de 2009, besides having the command of the standard form of the English language, students should be able to build, make meaning of concepts, select, interpret, organize, and make relations of information in a way to bring solutions to daily problems. Therefore, studentscould change, in a supportive way, the reality around them considering the sociocultural diversity of the context. The ENEM proposal, according to the Matriz, predicates that the knowledge objectives contemplated by the ENEM reflect high schools reality and students are able to do the test, as the test respects the current stage of high school students. We have also realized that there are divergences in the types of literacy proposed: on the one hand, we have the MEC resolution to ENEM and the OrientaçõesCurriculares para o Ensino Médio (OCEM) using a more critical approach to foreign language learning in high schools, which for Street (1984) is based on a more culturally sensitive and contextual vision of literacy practices. On the other hand, we have traditional approaches used by some schools considering the English language learningas a traditional form of literacy in which only teachers have knowledge. We also understand that, despite the fact that OCEM and the Matriz Referencial para o ENEM are different documents, they have similar proposals for critical literacy. This paper uses a qualitative research methodology and an ethnographic approach to the observation ofan English class in a regular school situated in Belo Horizonte, Minas Gerais. Supported by proposals for ideological literacy by Street (1984) and the tridimensional model proposed by Lankshear, Snyder and Green (2000), the objective of this research is to present distinctions and congruences between the proposals by MEC for ENEM, theOCEM, and the reality observed in a high school English class. Therefore, we are going to show how the school uses the institutional documents as a literacy model to the learning process. Therefore, we believe that students must be their own agent in the learning process and start to see the process of entering federal universities as a form of preparation, not only for academic life, but to become an engaged citizen and to be ableto contribute and make changes in their society.